(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article deals with the poetry of Karakalpak-born Kazakh poet Rakhmet Ayapbergenov, his literary career, the themes of his poems, peculiarities of depicting his love for the nature of the motherland.